Penyuluhan Perawatan Metode Kangguru terhadap Peningkatan Suhu Badan Rendah Bayi Baru Lahir di RSUD Sawerigading Kota Palopo Tahun 2024 - Arifa Usman; Ayu Irawati; Susianti Susianti; Rismawati Rismawati (Pusat Riset dan Inovasi Nasional, 2024)
Sawerigading Hospital is located in the middle of Palopo City where the location is very strategic and easy to reach by the community, so it is not surprising that Sawerigading Hospital is in great demand by the people of Palopo City to get health service facilities. The method used in this community service activity is a group discussion with an interactive question and answer session between helpers and mothers for 40 minutes. The mothers are all postpartum mothers at Sawerigading Hospital, Palopo City, with a total of 30 mothers. Before the educational activity, a pre-test was carried out and after the activity a post-test was carried out using a questionnaire containing 10 questions about the importance of the kangaroo method. This activity was carried out at Sawerigading Hospital, Palopo City. Kangaroo Method Treatment (FMD) is skin contact between mother and baby early, continuously and combined with exclusive breastfeeding. The purpose of this community service is to increase the knowledge of mothers and mothers of.